2003
DOI: 10.4141/p01-202
|View full text |Cite
|
Sign up to set email alerts
|

Winter weathering effects on corn grown for grazing in a short-season area

Abstract: G. W. 2003. Winter weathering effects on corn grown for grazing in a short-season area. Can. J. Plant Sci. 83: 333-341. Winter grazing can reduce over-winter feeding costs of beef cows and, recently, the selection and marketing of corn (Zea mays L.) varieties for grazing has increased the interest of Alberta beef producers. The objective of this study was to compare grazing corn varieties with early conventional corn hybrids for winter grazing potential. Five corn varieties (one grazing, one short-stature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
2
6
1
Order By: Relevance
“…Protein content was higher for barley (10.3 to 14.3% CP) than the 3 corn hybrids (6.8 to 9.3% CP). The latter CP values were in agreement with those of previous work (Baron et al, 2003;Abeysekara et al, 2013) for corn forage. Taking into consideration the protein requirements of beef cattle, in the current study, only AC Ranger barley had sufficient amounts of CP required by gestating and lactating cows.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Protein content was higher for barley (10.3 to 14.3% CP) than the 3 corn hybrids (6.8 to 9.3% CP). The latter CP values were in agreement with those of previous work (Baron et al, 2003;Abeysekara et al, 2013) for corn forage. Taking into consideration the protein requirements of beef cattle, in the current study, only AC Ranger barley had sufficient amounts of CP required by gestating and lactating cows.…”
Section: Discussionsupporting
confidence: 82%
“…This rule says that for a mature beef cow to maintain her body condition score through the winter, the ration must have a TDN energy reading of 55% in mid pregnancy, 60% in late pregnancy and 65% after calving (Yurchak & Okine, 2004). Therefore, even accounting for weathering effects on plant material for winter grazing (Baron et al, 2003) , the result of the current study suggested that all three new corn hybrids had adequate energy needed by dry gestating cows, mid pregnancy cows, as well as late pregnancy cows at all sites. This further confirms that similar with barley, corn is a high energy feed that will normally match the nutritional needs of a dry cow in mid and late pregnancy and after calving.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Plots were seeded directly into standing stubble using a low disturbance no-till plot seeder with a row spacing ranging from 20 to 30.5 cm except at Melfort, where the plots were seeded into tilled soil. The stubble was canola at Canora in 2003and at Indian Head in 2002, spring wheat at Indian Head in 2003, Redvers in 2002and 2003, and Scott in 2003, and barley at Loon Lake in 2003and Canora in 2002. Seeding rates were 34 kg ha -1 for pearl millet and 22.5 kg ha -1 for proso millet, foxtail millets and sorghum-sudangrass.…”
Section: Methodsmentioning
confidence: 99%
“…Swath grazing and the grazing of standing corn (Zea mays L.) are two production practices that are currently being used on the Canadian prairies (Baron et al 2003;Anonymous 2004). Several studies have shown that swath grazing will reduce feeding costs for spring-calving beef cows and wintering calves (Volesky et al 2002;).…”
mentioning
confidence: 99%